Comparative capabilities of the speckle-tracking echocardiography technologiesin two-dimensional and three-dimensional modes in the detection of subclinical cardiotoxicity in patients with breast cancer - M. A. Saidova; A. A. Avalyan; E. V. Oshchepkova; V. N. Shitov; I. E. Chazova (Терапевтический архив, 2020)
Aim.The study was to assess the deformation properties of the left ventricle (LV) myocardium in patients with breast cancer initially and after anthracycline chemotherapy according to 2D and 3D speckle-tracking echocardiography (STE).